Reconstruction of landscaping and planting of residential developments of the 70-80s. in the south-east of Karaganda city - Dxomane, И.А.; Borisevich, Ю.А. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2024)
The article discusses the issues of reconstruction of green spaces and improvement of typical courtyard spaces that do not meet the modern needs of residents and the qualities of a modern living environment. The main problems of the study are the spontaneity of parking, the impersonality of the territory, and the lack of differentiation of the yard into zones for diverse social activities. Without clear functional zoning of a residential yard, the potential of empty spaces is devalued, which leads to a deterioration in the environmental and aesthetic qualities of residential areas, desolation and the “dying away” of green recreation areas. The comfort and safety of the microclimate of residential areas are the basis for the formation of a harmonious environment in multi-storey residential buildings. During the study, a questionnaires and surveys of neighborhood residents were conducted, as well as a functional analysis of existing residential areas. Based on aforementioned information and analogues of landscaping and improvement of residential courtyards in South Korea, conclusions are drawn regarding the similarities and differences in approaches, and a conceptual proposal is formed. The concept for the reconstruction of a residential courtyard is a unified system of principles for humanizing the city’s residential environment with minimal means of improvement, using “reserve territories” and regional natural and climatic features.